STUDI DESKRIPTIF KEMAMPUAN INTERAKSI SOSIAL ANAK AUTISM SPECTRUM DISORDER (ASD) DI SEKOLAH HOMESCHOOLING SUKACITA BANJARMASIN - Surya Citra Ma’ruf; Miftahul Aula Sa’adah (CV. ADIBA ASIHA AMIRA, 2026)
This study aims to describe the social interaction skills of children with Autism Spectrum Disorder (ASD) at the Sukacita Homeschooling School in Banjarmasin and to identify the factors that influence them. The study employed a qualitative approach using a descriptive case study design. The research subjects comprised three children with Autism Spectrum Disorder (ASD) (AT, MFR and MFA), whilst supporting informants included three teachers and three parents. Data were collected through observation, in-depth interviews and documentation, and were subsequently analysed using the Miles, Huberman and Saldaña model. The research findings indicate that the social interaction skills of the three subjects still vary and are influenced by several key factors identified. The findings include mood and emotions, which influence a child’s readiness to engage in social interaction; communication limitations, which affect a child’s ability to initiate, maintain and understand social interactions; family and school environment support, which plays a role in facilitating the development of a child’s social interaction skills; the duration of therapy, which contributes to the development of social interaction skills at different rates for each subject; and opportunities for social interaction, which influence the child’s ability to adapt and form relationships with others. The findings indicate that the development of social interaction in children with ASD is influenced by interrelated factors; therefore, consistent environmental support, adequate opportunities for interaction, and interventions tailored to individual needs are required to optimise the development of children’s social interaction.